Design And Application of an Administrative Panel for Managing the Employees Activities of a Research and Teaching Unit: The Case of Employee Evaluation System at Czestochowa University of Technology, Poland - Szymon BERSKI; Kamila PASTERNAK (Communications of International Proceedings, 2025)
The article presents the structure, organisation and examples of operation of the university employee activity administrator panel, which is the main element of the employee evaluation system (EES) at Czestochowa University of Technology (CUT). EES consists of a database server based on PostgreSQL and LibreOffice Base (LO Base) software, which is part of the LibreOffice suite. The pgAdmin4 v.9.2 for Chrome Browser database management software was used to test individual solutions at the design and validation stage, which enabled the design and creation of employee evaluation form templates, as well as the use of the macro language to build advanced queries in forms and work with LO Base subforms. This paper extends this system to include a panel for administering employee activity (AEP) and also describes modifications to the database schema on which the EES system is based. Moreover, the usefulness of the created system in the management and administration environment of higher education institutions was demonstrated in the area of ​​employee evaluation and human resources management as well as in the area of ​​organisational security in terms of continuity of access to the system, data security and software servicing.
Keywords: PostgreSQL; LibreOffice Basic scripts; open-source software; organisational security